2006
DOI: 10.2106/jbjs.e.01454
|View full text |Cite
|
Sign up to set email alerts
|

Physical Therapy Alone Compared with Core Decompression and Physical Therapy for Femoral Head Osteonecrosis in Sickle Cell Disease

Abstract: In this randomized prospective study, physical therapy alone appeared to be as effective as hip core decompression followed by physical therapy in improving hip function and postponing the need for additional surgical intervention at a mean of three years after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 36 publications
1
58
1
3
Order By: Relevance
“…Treatment options have continued to evolve for osteonecrosis and include potential nonoperative pharmacotherapies (such as anticoagulants, bisphosphonates, shockwave therapy, or hyperbaric oxygen) [5,6,16,17,23,24,43,52,68]; joint-preserving surgeries (core decompression and various vascularized and nonvascularized bone grafting procedures) [18,35,36]; and joint-replacing surgeries, including THA. Although numerous treatment algorithms have been proposed to provide guidance to the treating physician [18,19,45,58,64], controversy remains surrounding the most appropriate surgery and at what stage of the disease process these procedures should be performed [9,10,34,50,59,60].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment options have continued to evolve for osteonecrosis and include potential nonoperative pharmacotherapies (such as anticoagulants, bisphosphonates, shockwave therapy, or hyperbaric oxygen) [5,6,16,17,23,24,43,52,68]; joint-preserving surgeries (core decompression and various vascularized and nonvascularized bone grafting procedures) [18,35,36]; and joint-replacing surgeries, including THA. Although numerous treatment algorithms have been proposed to provide guidance to the treating physician [18,19,45,58,64], controversy remains surrounding the most appropriate surgery and at what stage of the disease process these procedures should be performed [9,10,34,50,59,60].…”
Section: Introductionmentioning
confidence: 99%
“…Yamaguchi et al reported that treadmill running after transplantation of bone marrow-derived MSCs can promote cartilage regeneration [39]. Some mechanical stimulations, such as ultrasound and gravity force, also promote cell differentiation and proliferation [41,42]. Biomechanical, biophysical, physiological, and radiological knowledge are essential in designing the protocol for musculoskeletal rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanical, biophysical, physiological, and radiological knowledge are essential in designing the protocol for musculoskeletal rehabilitation. However, treatment programs for ONFH without cell therapy have not been improved since the report of Neumayr et al [42]. Developing a rehabilitation program is important.…”
Section: Discussionmentioning
confidence: 99%
“…Even though Physiotherapy has been seen to improve and efficiently treat musculoskeletal dysfunctions in SCA patients. 3,31 According to 32 majority of sickle cell patients managed with chemotherapy alone were seen as very unstable, hence, the recent development and treatment concepts advocate combination of several types of therapies other than chemotherapy alone, especially as regards joints pain and pain crisis. Therefore management of SCA requires holistic interdisciplinary evidence-based approaches.…”
Section: Discussionmentioning
confidence: 99%